Tinjauan Perjanjian Internasional Terhadap Kerja Sama Mikro - Ezra Raphael Timotius; Popi Tuhulele; Dyah Ridhul Airin Daties (Faculty of Law Universitas Pattimura, 2023)
International Treaties are sources of international law that have the basis of international legal force. Countries in the Southeast Asian region agreed to create a safe and peaceful atmosphere for the region by forming an organization called ASEAN. ASEAN formed the ASEAN Economic Community (AEC) which is a form of economic integration in the Southeast Asian region. AEC aims to assist ASEAN integration through AEC (ASEAN Economic Community). Each ASEAN member country pays attention to strategies, policies for the empowerment of MSMEs, including in Indonesia. The purpose of the study is to analyze and know about ASEAN cooperation, especially AEC in Micro Cooperation (MSMEs) in ASEAN and to analyze and find out the implementation of MSME micro cooperation agreements implemented in Indonesia. This research method used is normative juridical. The problem approach used is a legal approach and a conceptual approach. The sources of legal materials are primary, secondary, and tertiary. Collection of legal materials using literature studies. Furthermore, the analysis of legal materials on MSME trade, ASEAN, and their relationships in International Agreements is analyzed and processed systematically so that the results are expected to answer this research problem. The results of the study found that the AEC cooperation relationship has a positive impact on MSME microeconomic cooperation in ASEAN. The presence of AEC is the basis and legal basis, important for MSME microeconomic cooperation. The implementation of the AEC cooperation agreement for Indonesian MSMEs has been going well, but there are still several obstacles that need to be overcome. These problems are related to funding, availability of natural resources, and lack of human resources. These things are still a challenge for Indonesia in competing with other countries.